2017
DOI: 10.3906/biy-1610-6
|View full text |Cite
|
Sign up to set email alerts
|

The jasmonate-ZIM domain protein FtJAZ2 interacts with the R2R3-MYBtranscription factor FtMYB3 to affect anthocyanin biosynthesis in tartary buckwheat

Abstract: Tartary buckwheat is a type of coarse cereal that contains a rich supply of flavonoids. When suffering from certain stresses, tartary buckwheat can respond by promoting the biosynthesis of anthocyanins. It is well established that the jasmonate (JA) signaling pathway plays a critical role in plant resistance to disease by stimulating the production of anthocyanins; furthermore, the genes encoding the jasmonate-ZIM domain (JAZ) proteins have been shown to be key players in this process. However, the role of JAZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…We also found that FtMYB3 represses the transcriptional activation activity of P AtDFR and P FtDFR2 , indicating that FtMYB3 may also directly target these genes. In addition, our previous studies have shown that FtMYB3 can interact with the jasmonate-ZIM domain protein FtJAZ2 to affect anthocyanin biosynthesis [ 33 ]. Notably, we found that FtMYB3 was strongly induced by MeJA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that FtMYB3 represses the transcriptional activation activity of P AtDFR and P FtDFR2 , indicating that FtMYB3 may also directly target these genes. In addition, our previous studies have shown that FtMYB3 can interact with the jasmonate-ZIM domain protein FtJAZ2 to affect anthocyanin biosynthesis [ 33 ]. Notably, we found that FtMYB3 was strongly induced by MeJA.…”
Section: Discussionmentioning
confidence: 99%
“…The latest studies showed that FtMYB8 and FtMYB18 from the SG4-like MYB subfamily act as a negative regulator of anthocyanin/PA biosynthesis [ 31 , 32 ]. Additionally, our previous study showed that FtMYB3 interacted with the jasmonate-ZIM domain protein FtJAZ2 to influence anthocyanin biosynthesis in Tartary buckwheat [ 33 ]. Furthermore, FtMYB3 is likely to be involved in anthocyanin biosynthesis in the hairy roots of Tartary buckwheat [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research into gene transformation in Tartary buckwheat focused on transcription factors (TFs) of the MYB family, which are common in plants [103]. Jasmonites (JAs) are plant hormones known to induce the biosynthesis of different secondary metabolites.…”
Section: Msmentioning
confidence: 99%
“…Transcriptional repressors, jasmonate ZIM domain (JAZ) proteins interact with different TFs that have various roles in regulating JA-responsive expression of genes [104]. For example, genes which encode JAZ are the integral factor in the anthocyanin synthesis as a response to a certain type of stress [103]. Another one of the types that takes part in JA-induced biosynthesis of secondary metabolites is MYB type.…”
Section: Msmentioning
confidence: 99%
“…To date, more than 16 R2R3-MYB TFs involved in the flavonoid biosynthesis pathway have been isolated from Tartary buckwheat. For example, FtMYB24 positively regulates the accumulation of anthocyanins (unpublished data); FtMYB1, FtMYB2, and FtMYB23 promote the accumulation of proanthocyanidins; 17 FtMYB3 interacts with the jasmonate-ZIM domain protein FtJAZ2 and depresses the accumulation of anthocyanins under cold treatment; 18 FtMYB11, FtMYB13, FtMYB14, FtMYB15, and FtMYB16 negatively regulate rutin accumulation by interacting with "sensitive to ABA and drought 2" and FtJAZ1; 19 nidins. 20 However, only one MYB TF, FtMYB116, has been identified that specifically regulates rutin biosynthesis in Tartary buckwheat.…”
Section: Introductionmentioning
confidence: 99%